−20*z^2−21*z+6*z^3+70 =(-20*z^2+70) + ( 6*z^3-21*z) = -10*(2*z^2 -7) +3*z*(2*z^2 -7) = (3z-10)*( 2*z^2 -7 )
Можно разложить полностью , но тогда будет некрасиво :
(3z-10)*( 2*z^2 -7 ) =(3z-10)*(√2 *z -√7)*(√2 *z +√7)
Поэтому лучше оставить так :
−20*z^2−21*z+6*z^3+70 = (3z-10)*( 2*z^2 -7 )
−20*z^2−21*z+6*z^3+70 =(-20*z^2+70) + ( 6*z^3-21*z) = -10*(2*z^2 -7) +3*z*(2*z^2 -7) = (3z-10)*( 2*z^2 -7 )
Можно разложить полностью , но тогда будет некрасиво :
(3z-10)*( 2*z^2 -7 ) =(3z-10)*(√2 *z -√7)*(√2 *z +√7)
Поэтому лучше оставить так :
−20*z^2−21*z+6*z^3+70 = (3z-10)*( 2*z^2 -7 )